Teaching for purpose preparing students for lives of meaning - Malin, Heather (Harvard Education Press, 2018)
This book highlights for educators the role that purpose plays in youth development and in motivating students to develop cognitive as well noncognitive skills that teachers are seeking to instill.--Provided by publisher